Ispol'zovanie technologij vibroizobraženija dlja ocenki psichofiziologiceskogo sostojanija sportsmenov vysokoj kvalifikacii, specializirujušcichsja v pulevoj strel'be - Sturchak, I. S.; Abramova, T. F.; Nikitina, T. M.; Stashkevich, S. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The paper presents the results of using methods of vibration imaging, stabilometry and psychological testing to analyze the psychophysiological state of 16 highly qualified athletes specializing in bullet shooting. A statistical analysis of the parameters of the vibroimage of athletes in the conditions of performing the stabilometric tests of Romberg and Target is carried out. The informative significance of indicators determined using vibration imaging technologies was determined for assessing the psychophysiological state of athletes based on the identified relationship between the parameters of emotionsand psychophysiological conditions and the stabilometric parameters of maintaining equilibrium in Romberg and Target tests for highly qualified athletes specializing in bullet shooting.